بين الاقوامی قانون کی تشکيل : امام ابو حنيفہ کے افکار سے استفادہ کی ضرورت: FORMULATION OF INTERNATIONAL LAW: NEED OF GETTING GUIDANCE FROM IMAM ABU HANIFA’S THOUGHTS - Aslmi, Dr Nadeem Abbas; Muhammad Irfan Ahmad (Al Basirah, 2023)
Mutual relationships, cooperation, and unity among nations, societies, and states have always required international laws and regulations; otherwise, it is likely that there had been the situation of wars, fights, distrust, doubts, and nihilism. Therefore, The Holy Prophet (PBUH) made such comprehensive and omnibus universal laws and regulations so that all the nations can live in the best and most organized way to an extent. For ease and comprehensibility to Muslim Umma, Imam Abu Hanifa introduced a domain of knowledge based on Fiqh with the name Ilm al Siyyer. His (RA) sayings and practices have primary importance in making an Islamic international law. He (RA) accordingly, wrote a book on it. Later on, this domain of knowledge was also introduced by his followers like Muhammad Bin Hasan Shainbani in Kutb e Zahir ur Riwayah, Qazi Abu Yousaf in Al-asaar o Al-khiraaj and Hasan bin Ziada in Adab ul Alqazi o Kitaab ul khiraaj. Following them, we can get guidance from Imam Abu Hanifa’ s thoughts, which may help in strengthening mutual relationships, eradicating wars and hatred among nations and states, and extending the socio-economic, commercial, and economical interests of states to masses and masses to states. Furthermore, matters on war and peace and mutual contracts can be settled with the result of which protection of children, women, old people, ambassadors, religious leaders human life, and property during a war can be ensured, and in peace and in making agreements, construction and development of the nations and the countries can be safeguarded. It is due to the weaknesses in and non-enforceability of contemporary international laws, it is felt that Imam Abu Hanifa’s (RA) thoughts are needed to be utilized.